Social capital as a resource for in-service teacher development and support - Taylor, Maryke (University of the Free State, 2020)
According to literature, teachers can improve their learners‘ academic results by applying social capital in their teaching. However, through my experiences as a mentor, my participation in mentoring courses, and my study of appropriate literature, I identified a gap between practice and literature. Although theory regarding social capital and its application to education is well developed, as is theory about mentoring, explicit application of social capital in education, in the context of in-service professional development and support of teachers through mentoring, appeared to be absent. In an attempt to address this identified gap in practice, I modified my approach to mentoring mathematics teachers in previously disadvantaged, low quintile South African schools to focus on the promotion of social capital. I implemented this mentoring model, derived from a review of the literature and my four years‘ experience as part of the University of the Free State‘s School Partnership Project (UFS SPP). I adopted an informal, individual approach in which I primarily modelled using the domains of social capital implicitly, with some explicit discussion sessions as opportunity allowed. During the fourth year, I conducted the empirical part of this research in an attempt to address the identified gap in the literature. In order to investigate how I, in my role as a mentor, and the teachers whom I mentored, understood and applied social capital in the classroom, I employed a qualitative case study design. Data were collected by participant observation during my interactions with eight teachers from four low quintile schools involved in the UFS SPP mentoring programme. Data were collected using field notes made during classroom observations, reflective journaling, and semi-structured interviews. Data collection was continued until a point of data saturation was achieved. Thereafter, I used qualitative data analysis with a combination of inductive and deductive analyses. Bourdieu‘s theory on social capital was deductively used as analytical hook to construct consistent indicators for my research. While organising the data, I used inductive data analysis to form general sub-themes. The findings revealed that, by the fourth year of the programme, the teachers were still only using social capital to a minimal extent. I suggest that this is due to constraints of habitus and/or field, and that this underutilisation of social capital perpetuates these constraints. It appeared that some variations observed in both habitus and field were associated with some variation in using social capital, suggesting possible conditions under which such a mentorship programme is more likely to be successful. The significance of this research is the explicit explanation of the importance of social capital in teaching and learning; how it can be applied as a resource for optimal school education; and the value of social capital through mentoring teachers in in-service teacher development and support programmes. Furthermore, it accentuates the difficulty of the implementation of social capital in teaching and learning, pointing to the need for further research.
Keywords: Dissertation (M.Ed. (Higher Education Studies))--University of the Free State, 2020; Cooperation; Educational performance; Educational trust; Extended networks; In-service teacher training; Mentee; Mentor; Mentoring; Novice teachers; Obligation; Reciprocity; Safety; Self-concept; Social capital; Teacher leaders